1993
DOI: 10.1523/jneurosci.13-09-03669.1993
|View full text |Cite
|
Sign up to set email alerts
|

A system for characterizing cellular and molecular events in programmed neuronal cell death

Abstract: A model system has been established in which PC12 cells are converted to neuronal-like cells that undergo transcription-dependent cell death following removal of NGF. Nineteen sublines of PC12 cells were tested to establish parameters for making cells dependent on NGF for survival. In most sublines, a relatively small percentage of cells become dependent on NGF for survival, and following removal of NGF, most of the cells begin proliferating in serum-containing medium. In several sublines, however, a significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
203
0

Year Published

1996
1996
2003
2003

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 275 publications
(211 citation statements)
references
References 27 publications
8
203
0
Order By: Relevance
“…Indeed, rapid regeneration of sheared neurites from differentiated PC12 cells is regulated by translation of short-lived mRNAs, indicating that continual transcription is needed to maintain this injury response (38). Differentiated PC12 cells also require continual exposure to NGF to maintain their survival (47). Despite the need for continual exposure to NGF, most kinetic analyses of NGF signal transduction have shown that activities of its TrkA receptor and downstream protein kinases rapidly peak and then fall to seemingly undetectable levels within hours after ligand stimulation (11,23,34,48).…”
Section: Figmentioning
confidence: 99%
“…Indeed, rapid regeneration of sheared neurites from differentiated PC12 cells is regulated by translation of short-lived mRNAs, indicating that continual transcription is needed to maintain this injury response (38). Differentiated PC12 cells also require continual exposure to NGF to maintain their survival (47). Despite the need for continual exposure to NGF, most kinetic analyses of NGF signal transduction have shown that activities of its TrkA receptor and downstream protein kinases rapidly peak and then fall to seemingly undetectable levels within hours after ligand stimulation (11,23,34,48).…”
Section: Figmentioning
confidence: 99%
“…In an attempt to gain a better understanding of the molecular mechanism underlying the proapoptotic action of Bcl-x S in cancer cells and to compare it to that of Bax, we examined the e ects of Bcl-x S and Bax in the rat pheochromocytoma line PC12, a well characterized cellular model system commonly used for the study of neuronal apoptosis (see, e.g., Haviv et al, 1998;Pittman et al, 1993;Stefanis et al, 1996). Our results suggest that Bcl-x S and Bax di er in their apoptotic e ects in PC12 cells.…”
Section: Introductionmentioning
confidence: 99%
“…In serum containing medium these cells proliferate; however, when treated with nerve growth factor (NGF), cells stop proliferating and di erentiate into neural cells similar to sympathetic neurons (Greene and Tischler, 1976). Additionally, there are numerous apoptotic paradigms that have been established for PC12 cells, including those involving removal of trophic support (Greene, 1978;Batistatou and Greene, 1991;Pittman et al, 1993). Given that some studies have implicated aberrant or inappropriate cell cycle in the death of trophic factor deprived PC12 cells and sympathetic neurons (Batistatao and Greene, 1993;Rubin et al, 1993;Farinelli and Greene, 1996;Park et al, 1996), this system provides a means for testing the hypothesis that p21 expression would block death resulting from trophic factor removal.…”
Section: Introductionmentioning
confidence: 99%